Bio-ethanol Development from Domestic Waste - ZIKRI, MUHAMMAD AKIF; Nor Aira Zambri (Progress in Engineering Application and Technology, 2024)
Climate change, driven by carbon emissions from power plants using coal, gas, and oil, is a major concern. Renewable energy sources like water, wind, solar, and biomass can help reduce pollution. This project explores using domestic waste to produce bio-ethanol, which can replace fossil fuels for electricity generation. The project addresses the depletion of natural resources and waste management challenges. By assessing corn and rice as alternatives to fossil fuels and developing a process to convert domestic waste into bio-ethanol, the project aims to provide a sustainable energy solution. Methods include drying, blending, fermentation, and distillation. Results show that corn and rice are viable alternatives, and a sustainable bio-ethanol production process was developed. This method can reduce pollution and promote renewable energy use. In conclusion, producing bio-ethanol from domestic waste can support sustainable power generation, aligning with the global shift toward cleaner energy.